Survey of cysticercosis among school childrens at sekolah kebangsaan Bunohan Tumpat in Kelantan / Siti Aisha Binti Hassan - Hassan, Siti Aisha (Faculty of Health Sciences, 2007)
The objective of this study was to determine the exposure to cysticercosis among school childrens at Sekolah Kebangsaan Bunohan, in Tumpat Kelantan. Cysticercosis is caused by the presence of cysticercus (tapeworm larvae) of Taenia solium. Fortysix serum samples obtained from Siamese and Malay ethnic groups were analyzed using the Cysticercosis ELISA test kit (Cypress Diagnostics, InC). From the samples analyzed, five serum samples showed that IgG of cysticercosis positive was 11%. There were no positive cases among Malay students. This result indicated that only Siamese students are exposed to cysticercosis.